Perancangan Early Warning System Untuk Mendukung Sistem Persediaan Barang Dagang - Rahmat Rizal (Prosiding SISFOTEK, 2018)
Inventory of goods is an economic valuable resource that has an important role for a trading company. Inventory of goods needs to be managed properly to know the flow of goods inventory entry and entry so as to facilitate company management to make decision. In the management sometimes there are still many companies that have difficulty, either because they often run out of stock of goods or lack of information about the stock of goods that have decreased quality, such as expiration. Therefore, the authors are interested in trying to design a system that can provide early warning against these difficulties. This system is called Early Warning System to support inventory system. In the process the writer first analyzes the Early Warning System and then connect it to the inventory system. Then set the needs analysis of needs, and made the design of the system. The final result will be the design of the Early Warning System that can provide a warning in the form of reports on what items will run out and what items will expire.